Interent Usage among Female Undergraduates in Ferdowsi Univrsity, Iran - Joorabchi, Toktam Namayandeh (2009)
The importance of the public use of Internet has noticeably increased in people’s daily life. Internet, regarding its potential possibilities has attracted most Internet users’ prominent attention specially, students. The significant portions of students who use the Internet are females. They involve with the Internet based on their needs for accessing information, satisfying their leisure activities, transferring their information, making communication with others and so forth. This study was designed by applying the Use and Gratification theory framework to understand the Internet usage among female undergraduate students. The objectives of this study are to identify the relationship between the pattern of Internet usage, attitude towards Internet, English language knowledge, field of studies, Internet skills, problems and purpose of using Internet with the gratification of Internet usage. The present study used a survey design to achieve the objectives of the study. Non-probability sampling was employed in this study. The purposive sampling method was chosen for this study because the subjects were selected based on the specific demographical characteristics such as gender, age, education level, not working and using the Internet. A total of 319 respondents participated in the study in which 62 are from the field of English language and 257 from the other fields of humanities. Five categories of gratification for using the Internet were identified, namely, Escape, Affective, Cognitive, Social Integration, and Personal Integration. Most of the female undergraduate students used Internet for searching and getting knowledge. Finding relevant information for research was the most important purpose for students. They mostly search in Persian Google.com. The most common problem of using the Internet is that it takes too long time to download the Internet pages. The most common gratification of using the Internet was related to information gathering and learning new things. This study found no significant relationship between numbers of years in using the Internet with gratification of Internet usage. However, the relationships between attitude, purpose and frequency of Internet usage with gratifications of Internet usage are significant and positive.